Pengaruh Reformasi Anggaran Dan Partisipasi Penyusunan Anggaran Dan Pengendalian Internal Terhadap Kualitas Anggaran Dengan Konflik Kepentingan Sebagai Variabel Pemoderasi (Studi Kasus Pada Pemerintah Daerah Tapanuli Utara) - Tambunan, Bonifasius H.; Sihombing, Halomoan S.; Saribu, Ardin Dolok (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of the research is to find out the impact of the relationship between budget reform and participation in budget formulation and internal control on budget quality and conflict of interest as a moderation variable. Research methods use quantitative methods of causal research. The results of the research are: Budget Reforms versus Quality of Significant Impact Budget, Participation in Budgeting versus Qualitative Impacts Budget, Internal Controls Versus Non-Significant Quality, and Conflict of Interest Versus Quality of Budget with Conflicts of Interests. While the influence of moderation on the quality of budget reforms is not defined as a moderation variable, moderation of interest conflicts is defined by moderation as a variable of quality.